Daily Social Life of Older Adults and Vulnerabilities During the COVID-19 Pandemic - Chen, Jen-Hao (Frontiers in Public Health, 2021)
Introduction: The social integration of older adults is crucial for understanding their risk of infection and mental health during the COVID-19 pandemic. However, the social lives of older adults differ, which means they are not all vulnerable to COVID-19 in the same way. This study analyzes everyday time use and social contacts of older adults to inform discussions of their vulnerabilities during the pandemic. Methods: Using the 2019 American time use survey (N = 4,256, aged 55 and older), hurdle model regressions were used to examine the relationship between age, gender, and six indicators of the degree of social contact and time use, including (1) time alone, (2) time spent with family members, (3) time spent with non-family members, (4) time spent with people in the same household, (5) number of public spaces visited, and (6) time spent in public spaces. Results: Results showed substantial heterogeneity in everyday time use and social contacts. Time in public places gradually decreased from the oldest-old (85 years or older), old-old (75–84 years), to mid-life (55–64 years) adults. The gaps were not explained by age differences in sociodemographic characteristics and social roles. Compared with mid-life adults, time with family members of the young-old and old-old adults decreased, but time with non-family members increased. Age differences in social roles over the life course partially explained the differences. Conclusions: Should these patterns of time use and social contacts persist during COVID-19; then, such variations in the organization of social life may create different exposure contexts and vulnerabilities to social distancing measures among older adults; such information could help inform interventions to better protect this population.